ANALISIS INDEKS KUALITAS LINGKUNGAN HIDUP DI KOTA MANADO - DOTULONG, JACKY; POLII, BOBBY; PAKASI, SANDRA (Sam Ratulangi University, 2020)
Environment is an importan issue and complex. The rate of population growth and developmentgreatly affects the quality of the environment in Manado City. Environmental quality is an environmentalcondition that can provide optimal carrying capacity for human survival in an area. Environmental qualityincludes water quality, air quality, and land cover quality. This study aims to analyze the EnvironmentalQuality Index in Manado City which includes the Water Quality Index, Air Quality Index, and Land CoverQuality Index.The method used in this research is descriptive quantitative. Measurement of water quality was carriedout in three major rivers in Manado City, namely the Tondano River, the Sario River, and the MalalayangRiver. From each river, measurements of water quality were carried out at two points, including theupstream and downstream areas with the measured parameters TDS, TSS, BOD, COD, and DO. Analysisof water quality using the Pollution Index (PI) method and then converted into the Water Quality Indexvalue. Measurement of air quality were carried out at three points, including office, transportation, andresidential areas with parameters measured as SO2 and NO2. Analysis of air quality using a calculation ofthe European Union (EU) model of Air Quality Index and then converted into an Air Quality Index value.Measurement of land cover quality is carried out by calculating the land cover index, namely measuring thearea of Manado City and the area of green land or forest using ArcGIS Software. The land cover value isobtained from the division between the area of green land or forest and the area of Manado City and thenconverted into the Land Cover Quality Index value. Analysis of Environmental Quality was carried out bycalculating the Environmental Quality Index in Manado City, namely the value of the Water Quality Index(30%), Air Quality Index (30%), and Land Cover Quality Index (40%).The quality of water in Manado City based on the parameter test showed a decrease in quality wherethe parameters of BOD, COD, and DO exceed the quality standards according to PP 82 of 2001 while thestatus of water quality in the mildly polluted category was based on KepMen LH 115 of 2003. The value ofthe Water Quality Index obtained 80. The Quality of Air in Manado City based on the results of monitoring,the highest values of SO2 and NO2 in the transportation area. The value of the Air Quality Index obtained30,56. The Quality of Land Cover in Manado City is based on the calculation of the Land Cover Indexobtained 0,72. The Land Cover Quality Index value obtained 89,60. The results of the EnvironmentalQuality Index value for the City of Manado obtained 69 with the predicate Fairly Good.Based on the results of the study, it can be concluded the Environmental Quality Index in Manado Cityis fairly good. It is recommended for Manado City Goverment in achieving a better environmental conditionneeds to increase activities that are managing and providing protection for the environment in Manado City.Keywords: Environmental Quality Index